Leadership in Action: Executive Effectiveness and Fulfillment: A Leadership Factor - Lee, Robert; King, Sara (Center for Creative Leadership, 1999)
In order to bring your full resources to bear on leadership challenges, your personal life and work life must be well integrated, and this will likely require you to make changes in both.